THE INFLUENCE OF TECHNOLOGY-BASED MEDIA OF DIGITAL JAVANESE SCRIPT AMONG JUNIOR HIGH SCHOOL STUDENTS - Hilma Oktaviana Fajrin (Jurnal Ilmiah WUNY, 2023)
The impact of advances in digital technology has eroded the existence of the Javanese language as one of the regional languages used in Indonesia. The Javanese Script, an important component of the Javanese language, is less attractive to the younger generation. Digital literacy can be used to develop culture because it fits the characteristics of the current generation as digital natives. Now, people can write Javanese scripts using a computer because the Javanese Script has been successfully included in the digital standard writing system (Unicode) since 2009. This is also utilised by developing a Javanese script keyboard called Aksaraya which can be installed on the IPad. The method chosen in this research is quasi-experimental. It was carried out by giving treatment with Aksaraya media to reveal its influence through a pretest-posttest control group design experimental design. The analysis in this study is the Paired sample T-Test with the help of SPSS 21 for windows. In this study, the population used was SMP Negeri 4 Pakem, while the sample taken was the eighth-grade students. Their conceptual understanding of data is gained from tests conducted before and after using digital-based Javanese script learning media. The analysis showed that the students' mean scores after using digital-based Javanese writing learning media were higher (80.05) than before (60.96). It showed the correlations (0.670) that indicated a strong relationship with Sig. (0.000) ˂ α = 0.05. It can be concluded that Aksaraya learning media significantly influences students' learning results.